AUDIT TEKNIS PEMBANGUNAN JEMBATAN AIR HITAM PUJUD KABUPATEN ROKAN HILIR - Sugeng Wiyono; Yollyadriati, Yollyadriati; Vivi Ekayanti (Nusantara Hasana Journal, 2025)
This Technical Audit of the Air Hitam Pujud Bridge construction in Rokan Hilir Regency contains the audit's basis, field implementation methods, implementation results, and conclusions and recommendations for the project. The Technical Review included checking the work volume and quality based on a joint field survey, as well as direct quality control of several work samples at a laboratory, including the Islamic University of Riau.